Analisis Faktor Penyebab Distorsi Harga Pasar dan Penanggulangan Dampaknya dalam Perspektif Islam - Fachrounissa Zein Vitadiar (Universitas Muhammadiyah Surabaya, 2023)
The market balance is created based on a fair and correct market mechanism. In Islam, one form of making an ideal market is that there is no price intervention that makes prices soar even more. However, the conditions in the field today are far different from the Islamic market concept, in which there are many problems originating from internal and external factors so that the impact on the circulation of economic activity is hampered. Therefore, this study aims to find out what are the causes of price distortions in the Islamic market and how to overcome them. The research method used in this research is descriptive qualitative with a literature study approach obtained from books, journals, articles that support the focus of this research. The results obtained are that price distortions are caused by several things including cartels and merchant associations, ikhtikar, talaqqi ruqban, tadlis, taghrir, and bay najasy. To restore market stability to normal conditions, the role of the government, hisbah institutions and moral awareness of market participants is needed, so that no party feels oppressed and all can benefit from the existence of the market.